Screening of some nigerian plants for pyrrolizidine alkaloids - A. Dare, T.; Nwude, N.; I. Rekwot, P.; Mamman, M.; O. Omontese, B. (Scientific Journal of Animal Science, 2013)
Pyrrolizidine alkaloids (PAs) are an important class of plant toxins whose hepato- and pneumo-toxicity have been extensively studied. Twenty three field plant materials (leaves, flowers, pulp, seeds) were collected, identified and screened for unsaturated PAs. A field test method with Ehrlich reagent was used. The absorbance of Ehrlich colour of the PAs and N-oxides were obtained at 565nm. Positive reactions were obtained from Borreria verticillata; Guiera senegalensis; Tamarindus indica; Crotolaria doniana; C. gorensis; C. glaucoides; C. mucronata; C. naragutensis; C. lachnosema and C. retusa. The occurrence of PAs are reported for the first time in C. doniana and C. glaucoides. B. verticillata, G. senegalensis and T. indica gave positive Ehrlich reactions which could be due to PAs or other groups giving positive Ehrlich reaction. A number of medicinal and food plants gave negative Ehrlich reaction. Further work is required to confirm and identify the alkaloids in the plants that gave positive reactions.